Rancang Bangun Simulator Pengenalan Suara Ucapan untuk Gerakan Mesin CNC - Herry Sujaini; Arif Bijaksana PN. (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
This research target is to develop a simulator program to arrange the movement ofmachine CNC932, where the command conducted by speech. Examination conducted to seethe ability of system to translate of speech input for the movement commands of machineCNC932. Attempt to simulator done by giving 7 available commands conducted by 3 peopletester as much each 20 times.Before doing attempt tester trained their voice to program. Commands given by testerpass the microphone consisted of